Tall shrub (Alnus, Betula, Juniperus, Salix, and Shepherdia) densities at Brooks Range treelines, Alaska (2019-2022) ... - Dial, Roman; Wong, Russell; Maher, Colin; Hewitt, Rebecca; Sullivan, Patrick (NSF Arctic Data Center, 2023)
Stem counts of tall shrubs (height from 0.3 to greater than 2 meters) during 2019, 2020, 2021 and 2022 as sampled within n = 594 5-meter radius plots (area = 78.5 square meters), each centered on a selected white spruce adult called "Focal Tree". The purpose of this dataset was to examine spatial variation in tall shrub densities of the most important genera across the Brooks Range and in relation to local microclimates. It also provides a baseline for future shrub stem counts to determine changes in abundance. ...